EFFECT OF VEGETATION ON THE DIVERSITY AND COMMUNITY STRUCTURE OF INSECT POLLINATORS OF SUGAR PALM (Arenga pinnata) IN SOUTH TAPANULI - Siti Hardianti Wahyuni; Retna Astuti Kuswardani; Zulheri Noer (Universitas Nias Raya, 2026)
Sugar palm (Arenga pinnata) is an important agroforestry commodity whose productivity depends heavily on insect-mediated pollination. Vegetation type influences pollinator availability by shaping habitat structure and resource distribution. This study aimed to analyze the effect of vegetation types on the diversity and community structure of insect pollinators of sugar palm in South Tapanuli Regency, Indonesia. A quantitative comparative-ecological design was applied in two vegetation types, namely secondary forest and open land. Data were collected using direct observation and sweep netting during the flowering period and analyzed using the Shannon–Wiener diversity index, evenness, Simpson’s dominance index, regression, and NMDS ordination. Results showed that pollinator abundance was higher in open land, while secondary forest supported higher diversity (H’ = 2.87–3.12) and evenness, with lower dominance values. In contrast, open land was dominated by a few adaptable species. NMDS analysis indicated differences in community composition between vegetation types. Regression analysis showed a weak and non-significant relationship between abundance and diversity (r = −0.022; p > 0.05), indicating that higher abundance does not necessarily reflect higher diversity. In conclusion, vegetation complexity enhances pollinator diversity and community stability, whereas habitat openness increases abundance but reduces ecological balance. These findings highlight the importance of maintaining heterogeneous landscapes to support sustainable pollination services for Arenga pinnata.